Online Learning and Effective Communication During The Pandemic - Despitasari, Ni Wayan Putri; Joni, I Dewa Ayu Sugiarica (Jurnal Pustaka Komunikasi, 2025)
It has been reported in the literature that students experience a variety of communication difficulties while participating in online learning, both among themselves and with instructors. During this pandemic, as is widely known, extensive research on online learning has been carried out in order to better understand it. Research on communication between lecturers and students, on the other hand, is still extremely scarce. As a result, the purpose of this study is to determine whether effective communication between lecturers and students has occurred in online learning. The quantitative nature of this study is demonstrated by the use of a five-point Likert scale online questionnaire with six closed-ended questions. An analysis of the data collected from 500 student participants representing public and private universities was carried out quantitatively using the descriptive statistics method. When it comes to online learning environments during the COVID-19 pandemic, the findings show that participants have a generally positive experience with them, according to the findings. The fact that their classes are conducted online does not prevent them from maintaining effective communication and interaction with their classmates and lecturers. This demonstrates the efficiency with which online classroom communication can be conducted. The current study's implications and limitations are also discussed.